1985
DOI: 10.1037/0022-006x.53.3.424
|View full text |Cite
|
Sign up to set email alerts
|

Children's Depression Inventory: Sex and grade norms for normal children.

Abstract: Normative data for the Children's Depression Inventory were collected on 1,463 public school children in Grades 2 through 8. Significant sex and grade differences were obtained, but the absolute magnitude of these differences was small. Scores were very consistent with those previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
100
2
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 8 publications
21
100
2
3
Order By: Relevance
“…When comparing the elementary and high school samples on level of need satisfaction, third graders reported experiencing significantly higher levels of competence and relatedness than their seventh grade counterparts. Consistent with previous literature (Finch, Saylor, & Edwards, 1985;Garrison, Jackson, Marsteller, McKeown, & Addy, 1990;Scheidt et al, 2000), the elementary school sample had less depressive symptoms and more positive affect, than the high school sample.…”
Section: Adolescentssupporting
confidence: 80%
“…When comparing the elementary and high school samples on level of need satisfaction, third graders reported experiencing significantly higher levels of competence and relatedness than their seventh grade counterparts. Consistent with previous literature (Finch, Saylor, & Edwards, 1985;Garrison, Jackson, Marsteller, McKeown, & Addy, 1990;Scheidt et al, 2000), the elementary school sample had less depressive symptoms and more positive affect, than the high school sample.…”
Section: Adolescentssupporting
confidence: 80%
“…The items are answered on a three-point scale. It has good test-retest reliability and validity (Finch, Saylor, & Edwards, 1985). Lucassen, & Emmelkamp, 2007) had good internal consistency in the present study (alpha = 0.93) and is answered on a three-point scale.…”
Section: Depressive Symptomsmentioning
confidence: 52%
“…Each response is scored as either 0 (asymptomatic), 1 (somewhat symptomatic), or 2 (clinically symptomatic), contributing to an overall CDI score that can range from 0 to 54. The scale has demonstrated excellent internal consistency in both clinical and nonclinical samples [a4.80; Finch et al, 1985;Ollendick and Yule, 1990;Smucker et al, 1986] and acceptable test-retest reliability identified in both clinical and nonclinical samples [Finch et al, 1987;Kazdin, 1987;Kovacs, 1992;Nelson and Politano, 1990].…”
Section: Methodsmentioning
confidence: 90%
“…Consisting of 27 self-report items, the CDI was modeled after the Beck Depression Inventory (BDI) [Beck, 1972;Beck et al, 1961] to assess affective, cognitive, and behavioral symptoms of depression in youth. The CDI has demonstrated excellent reliability [e.g., Finch et al, 1985], and broadly speaking, the CDI has demonstrated an adequate ability to distinguish between clinical and nonclinical groups of children [e.g., Fristad et al, 1987;Saylor et al, 1984]. For example, Saylor et al [1984] compared the CDI scores of psychiatric inpatients who manifested various clinical disorders to those of community schoolchildren and reported that the inpatient group scored significantly higher.…”
mentioning
confidence: 98%